Enhanced Secondary Metabolites Accumulation In Tetraselmis Suecica Via Nutrient Supplementation For Biological Evaluations Of Anti-oxidant, Anti-obesity, And Anti-inflammatory Properties - Shahril, Nor Shafiqah Nor (2024)
Microalgae are adaptive microorganisms with the capability to produce various functional secondary metabolites under controlled conditions. However, enhanced accumulation of secondary metabolites under the manipulation of carbon and nitrogen supplementations in microalgae cultivation are relatively underrepresented. In this study, a marine green microalga, Tetraselmis suecica was utilized to evaluate the effects of combined supplementation of carbon (molasses, glycerol, sodium acetate) and nitrogen (urea, ammonium sulphate and sodium nitrate) sources towards the secondary metabolites’ accumulation for biological evaluations. Briefly, the microalgae were cultivated in media with or without supplementation of carbon and nitrogen sources. The biomass was obtained, and the crude extracts were extracted using different organic solvents with increasing polarity (hexane, ethyl acetate, and ethanol). The total phenolic contents of crude extracts were quantified. Following this, the extracts of combined supplementations with higher biomass and phenolic contents were evaluated for the in vitro antioxidant, anti-obesity, and anti-inflammatory properties. The chemical profiling of extracts was carried out using Fourier-Transform Infrared spectroscopy (FTIR) and Liquid Chromatography with Mass Spectrometry (LC-MS). The results showed that combined supplementation of sodium acetate and sodium nitrate exhibited enhanced dry cell weight (1.095±0.03 g/L) and total phenolic contents (591.80±0.92 μg GAE/mg extract) in ethanol extract compared to control.